(untitled) (Experimental biology, 2015)
In this article are given generic and species keys of Polygonaceae Lindl. families determinant according to modern taxonomiccal system in the Kazakh language. In the family Polygonaceae Lindl. are 8 genus: Koenigia L., Rumex L., Oxyria Hill., Rheum L., Atraphaxis L., Calligonum L., Polygonum L., Fagopyrum Gaertn., and 187 species. Compiled keys definition of genus Koenigia L. are: K. islandica L. – 1 species, genus Oxyria Hill.: O. elatior R. Br. – 1 species, genus Rheum L.: R. nanum Siev., R. maximowiczii Losinsk., R. tataricum L., R. turkestanicum Janisch., R. wittrockii Lundstr., R. cordatum Losinsk., R. ompactum L., R. altaicum Losinsk., R. rhizostachyum Schrenk., R. reticulatum Losinsk. – 10 species, genus Atraphaxis L.: A. canescens Bunge, A. compacta Ledeb., A. karataviensis Lipsch. et Pavl., A. spinosa L., A. replicata Lam., A. laetevirens (Ledeb.) Jaub. et Spach., A. teretifolia (M.Pop.) Kom., A. pungens (M.B.) Jaub. et Spach., A. pyrifolia Bunge, A. decipiens Jaub. et Spach., A. muschketovii Krassn., A zeravschanica Pavl., A. frutescens (L.) Eversm., A. virgata (Regel) Krassn. – 14 species, genus Fagopyrum Gaertn.: F. sagittatum Gilib., F. tataricum (L.) Gaertn. – 2 species